Prevalence of fungal contamination in some of biology department’s laboratories - Shafiq, Shatha Ali; Aljuraisy, Y. H (Asian Journal of Pharmaceutical Research and Development, 2019)
Fungi are ubiquitous in distribution and are a serious threat to public health in indoor environments. The study was conducted to evaluate surface sampling in conjunction with air sampling for the detection of fungal contamination in Biology Department’s laboratoriesand determine the best detergent which treats with it. The study was carried out at the Biology Department, College of Science, Al-Mustansiriyah University, Baghdad. It was includes (i) isolation fungal samples on Potato Dextrose Agar (PDA) and identification these isolates by using morphological and microscopical characteristics and (ii) evaluation of three detergents on the most prevalent species of isolated fungi by using disk diffusion method and measuring the zone of inhibition against the tested isolate around each detergent.The results identified ten fungal species isolated from these laboratories, Alterneria sp., Aspergillusniger, Aspergillusflavus, Aspergillusterreus, Cladosporium sp., Penicillium sp., Rhizopus sp.,Fusarium sp., Geotrichum sp. andOxysporum sp.. Among all,Aspergillusniger was the more prevalent in all scanned laboratories. On the other hand, formalin when tested on A. nigerwas more effective than other detergents.We concluded that all tested laboratories had fungal contaminants due to numerous contamination sources. Formaldehyde fumigation will be very necessary to sterilize these laboratories.